Tertiary Students’ Difficulties in Combining English Clauses to Generate Complex Sentences - Pratiwi, Adhelia; Hidayah, Jumatul; Edy, Sarwo (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to describe tertiary students’ difficulties in combining English clauses to generate complex sentences. A descriptive quantitative method was applied by involving 30 tertiary English students at IAIN Curup as the samples. They were selected using a quota sampling technique. The present study revealed that many students (62.82%) had difficulties in combining between adjective clauses and independent clauses to generate English complex sentences. They also found it difficult to use subordinate connectors “who, whose, whom, and which” properly. Some students (42.64%) had difficulties in combining between adverbial clauses and independent clauses to generate English complex sentences. They found it difficult to use some subordinate connectors such as “after, if, before, nevertheless, nonetheless, and however” appropriately. Subsequently, many students (69.31%) had difficulties in combining between noun clauses and independent clauses to generate English complex sentences. They found it difficult to use subordinate connectors such as “what, where, why, whose, when, and how” properly. Further studies are expected to conduct experimentations and classroom-action research to help improve students’ English grammatical competence.Key words:Independent clause, dependent clause, complex sentence